Perancangan Sistem Pengelolaan Gaji Guru Dan Staff Berbasis Web Di SDIT Al-Fath Parung Panjang - Nugroho, Edi; Jabbar, Ilham; Rifqi Oktavian Nurcahyo, Muhammad; Lutfi Fuadi, Achmad (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
This research designs and develops a web-based teacher and staff salary management system for SDIT Al-Fath Parung Panjang using the Waterfall method. This system aims to automate the salary calculation and management process that was previously done manually, often causing errors. The Waterfall development stages applied include needs analysis, system design, implementation, testing, and maintenance. The result of this design is a web-based platform that is able to manage employee data, calculate salary components such as basic salary, allowances, deductions, and generate digital payslips. With the implementation of this system, it is hoped that SDIT Al-Fath can achieve higher operational efficiency, increased data accuracy, and transparency in salary management, as well as facilitate access to salary information for all teachers and staff.